Synthesis and characterization of iridium/platinum-hzsm5 catalyst for isomerization of n-pentane - Setiabudi, Herma Dina (2013)
Catalytic isomerization of n-alkane has been one of the important processes in petrochemical refining industry to increase the octane number of gasoline. This study investigates the catalytic activity of Ir/Pt-HZSM5 for n-pentane isomerization. The potential of iridium (Ir) as a catalyst for n-pentane isomerization was preliminarily investigated by using Ir-HZSM5. The result showed that Ir has a great potential to be used as a promoter, hence as a co-promoter for Pt-HZSM5. Ir/Pt-HZSM5 was prepared by impregnation of Ir on 0.1wt% Pt-HZSM5. The catalyst was characterized with X-Ray Diffraction (XRD), Surface Area Analyzer, Fourier Transformation Infra Red (FTIR), Nuclear Magnetic Resonance (NMR), Electron Spin Resonance (ESR) and X-Ray Photoelectron Spectroscopy (XPS). The acidity was determined by 2,6-lutidine adsorbed FTIR spectroscopy, while the catalytic activity was carried out in a microcatalytic pulse reactor. The results showed that Ir in the form of IrO2 was bonded to perturbed silanol groups. The presence of 0.1 wt% Ir slightly increased the acidity of Pt-HZSM5 and selectivity of isopentane. Ir enhanced the formation of protonic acid sites which participate in the isomerization, and inhibited the formation of hydroxyl groups which may participate in the enhancement of the cracking reaction. An increase in Ir loading (0-2.0 wt%) continuously decreased the acid sites. At low Ir loading, cracking process proceed through dimerization-cracking step, whereas high Ir loading reduces the contribution of dimerization-cracking step and promotes the contribution of hydrogenolysis. An increase in Si/Al ratio (23-280) decreased the number of strong acid sites which led to a decrease in the activity towards n-pentane isomerization. From the Response Surface Methodology (RSM) experiments, the optimum conditions for the n-pentane isomerization over Ir/Pt-HZSM5 were at treatment temperature of 723 K, treatment time of 6 h, reaction temperature of 548 K and flow of hydrogen over weight of catalyst, F/W of 500 ml g-1 min-1 in which the predicted value for the n-pentane conversion, isopentane selectivity and isopentane yield was 63.0%, 98.2% and 61.9%, respectively. The catalytic activity studies confirmed that n-pentane isomerization over Ir/Pt-HZSM5 strongly depending on the promotive effect of hydrogen. Ir/Pt-HZSM5 exhibited high stability during the coke removal process which was shown by the high activity of Ir/Pt-HZSM5 in the n-pentane isomerization after 90 pulses (30 h).